Space(s) of the Fantastic : a 21st century manifesto - Punter, David; Mancini, C. Bruna (London : Routledge, 2020)
This book provides a series of new addresses to the enduring problem of how to categorize the Fantastic. The approach taken is through the lens of spatiality; the Fantastic gives us new worlds, although of course these are refractions of worlds already in being. In place of real' spaces (whatever they might be), the Fantastic gives us imaginary spaces, although within those spaces historical and cultural conflicts are played out, albeit in forms that stretch our understanding of everyday location, and our usual interpretations of cause and effect. Many authors are addressed here, from a variety of different geographical and national traditions, thus demonstrating how the Fantastic - as a mode, a genre, a way of thinking, imagining and writing - continually traverses borders and boundaries. We hope to move the ongoing debate about the Fantastic forward in a scholarly as well as an engaging way.
OCLC-licensed vendor bibliographic record.
Keywords: Fantastic, The, in literature; Fantastic, The; LITERARY CRITICISM / Science Fiction & Fantasy